Analisis Perbandingan Efektivitas Dan Stabilitas Oksidasi Komposit Fe₃O₄/rGo, Fe₃O₄/Mxene, Dan Fe₃O₄/CNT Sebagai Material Penyerap Gelombang Radar - Tauhidah, Adzka Kamilah; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
This research focuses on a literature review regarding radar wave absorbing materials or Radar Absorbing Material (RAM) that uses Fe₃O₄-based composites with three main matrices, namely reduced graphene oxide (rGO), MXene, and carbon nanotubes (CNT). This topic is important because the ability of a defense system, whether air, sea, or land, in reducing radar detection is greatly influenced by the effectiveness of electromagnetic wave absorbing materials. Fe₃O₄ materials are known to have strong magnetic properties, while rGO, MXene, and CNT function as conductive materials that can increase absorption through dielectric loss and impedance matching mechanisms. By understanding the comparative characteristics of the three, it is hoped that it will be possible to determine which material is the most effective and stable for use in stealth applications in defense environments.